The state of muslim girls in physical activities and sport and significance of parenting in islamic perspective : (the case of Central and Southern Finland) - Shilpi, Manjuma Khanam (2012)
The role of young Muslim girls in sport activities in Western Europe seems a challenging circumstance which required more considerations, particularly in school settings according to previous studies report. The main objective of this study was to explore and investigate the available evidences regarding Muslim girls’ participation in sport and physical activities in the central and south Finland schools, as it is still remains with some unanswered questions. More specifically, the study tried to assess the participation of Muslim girls in physical and sport activities in schools; how parents perceive the school system regarding the P.E. lesson; what parents should do to let their girl’s participate in physical activities; and what should P.E. teachers do to facilitate Muslim girls in this regards. To answer the above research questions, a qualitative method particularly ethnographic study method was employed. The research was conducted in the central and southern Finland. In total six schools were purposely selected based on the attendance of Muslim girls. Both primary and secondary schools are included in this study. A total of 6 girls, 11 parents, and 6 respective P.E. teachers of the students were included. To gather relevant data for the study, following sources were used namely interview, participation observation, informal discussion, and document analysis were used. Semistructured interview guide was prepared and used for participating sport teachers, Muslim girls, and parents. The study revealed that Muslim girls are required to participate in all physical activities as other pupils do. However, most of the Muslim girls did not participate in public swimming pools because of Islamic moral values and obligations. The study showed that almost all parents expressed the importance of sport and physical education for Muslim girls; however, they emphasized the need to facilitate the religious obligations in schools. Regarding what the P.E. teachers should do to accommodate the needs of Muslim girls, the teachers showed their willingness to give value and respect the religious obligations of their students; however, they may not be able to fulfill all demands that are made by students unless the school system enforces clear rules in this regard.